Triggers of Escalations in Violence Against Civilians by Non-State Actors in Africa - Nyseth Nzitatira, Hollie (Terrorism and political violence, 2023)
Although past research has addressed why civilians are targeted, we know less about why non-state actors escalate violence against civilians at particular times. This article seeks to identify the events that trigger spikes in violence against civilians committed by non-state actors. We employ an innovative method to identify twenty-four such escalations in Africa committed by twenty different non-state groups between 1989 and 2015. Rigorous case studies reveal three major types of triggers, including situations in which (1) groups lose relative power, (2) groups gain relative power, and (3) opponents attack civilians. Specifically, we find that opponent military advances—which results in a relative loss of power for the non-state actor—are the most common trigger. More broadly, 75 percent of all escalations are tied to a group’s relative loss in power. These results improve understandings of civilian targeting by non-state actors and may inform efforts to forecast such violence before it occurs.